Singapore and the Global Recession - Ipnarski, Grzegorz (Singapur a globalna recesja, 2010)
The author looks at problems and decisions faced by Singapore in the light of the global recession which had its roots in the financial crisis of 2007. He analyses the deteriorating situation Singapore's economy found itself in at the time as the level of international trade decreased together with the global demand. He discusses the factors which caused this to be the harshest economic shock Singapore has experienced in over 20 years and explains why this had such a devastating effect on all sectors of the economy. The author also looks at micro- and macroeconomic policies used by the Singaporean Government to try to fight back the forces impeding growth and tries to comment to what degree these were successful.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 20-32
Keywords: Singapore; global recession; FDI; competitiveness; growth